Analisis Drug Related Problem terhadap Penggunaan Obat pada Pasien Geriatri di Puskesmas Kapanewon Kasihan Bantul - Margala Juang Bertorio; Agustina Agustina (Pelantar Press, 2025)
Drug Related Problems (DRPs) are significant concerns in medication management, particularly for geriatric patients who often experience polypharmacy and decreased physiological function. This study aims to evaluate the prevalence and impact of DRPs among elderly patients at Puskesmas Kapanewon Kasihan Bantul. The study aims to analyze the types and frequency of DRPs, their impact on the quality of life of elderly patients, and identify the factors contributing to DRPs. This descriptive cross-sectional study collected data using medication adherence questionnaires, DRP identification forms, and quality of life assessments with the EQ-5D scale. A total of 100 geriatric patients receiving prescription medications at the Puskesmas between 01 February and 31 March 2024 were included. Data were analyzed using descriptive and inferential statistics. Among 100 patients studied, 80% experienced one or more types of DRPs, with drug interactions (70%) and dosing errors (50%) being the most prevalent issues. 35% of patients reported significant adverse effects, and 10% showed non-adherence to prescribed medication regimens. Quality of life scores were significantly lower in patients with DRPs compared to those without DRPs, indicating a negative impact on quality of life. The findings highlight DRPs as a major issue in medication management for geriatric patients at Puskesmas. Polypharmacy, lack of understanding about medication use, and medication administration errors are key contributing factors. The decreased quality of life observed in patients with DRPs underscores the need for improved medication management and patient education. This study underscores the importance of evaluating and managing DRPs to enhance therapeutic outcomes and quality of life for elderly patients. Recommendations include enhanced patient education on medication use, routine therapy reviews, and additional training for healthcare professionals